Proceedings of the 23rd Pacific Basin Nuclear Conference, Volume 1 PBNC 2022, 1 - 4 November, Beijing & Chengdu, China - Liu, Chengmin (Springer Proceedings in Physics, 2023)
This is the first in a series of three volumes of proceedings of the 23rd Pacific Basin Nuclear Conference (PBNC 2022) which was held by Chinese Nuclear Society. As one in the most important and influential conference series of nuclear science and technology, the 23rd PBNC was held in Beijing and Chengdu, China in 2022 with the theme "Nuclear Innovation for Zero-carbon Future". For taking solid steps toward the goals of achieving peak carbon emissions and carbon neutrality, future-oriented nuclear energy should be developed in an innovative way for meeting global energy demands and coordinating the deployment mechanism. It brought together outstanding nuclear scientists and technical experts, senior industry executives, senior government officials and international energy organization leaders from all across the world. The proceedings highlight the latest scientific, technological and industrial advances in Nuclear Safety and Security, Operations and Maintenance, New Builds, Waste Management, Spent Fuel, Decommissioning, Supply Capability and Quality Management, Fuel Cycles, Digital Reactor and New Technology, Innovative Reactors and New Applications, Irradiation Effects, Public Acceptance and Education, Economics, Medical and Biological Applications, and also the student program that intends to raise students' awareness in fully engaging in this career and keep them updated on the current situation and future trends. These proceedings are not only a good summary of the new developments in the field, but also a useful guideline for the researchers, engineers and graduate students. This is an open access book.